From Meconomy to Weconomy and Back Again: Why the Sharing Economy Ultimately Just Merged with the Mainstream Economy - Bellotti Lyft, Victoria (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2018)
Human economic behavior arises from primal instincts for survival and, despite our higher aspirations, it seems we just can't escape this fact. History shows that ideologically inspired experiments in egalitarian economic systems have always stalled or utterly failed. Nevertheless, after the financial market crash of 2008, many tech entrepreneurs were bewitched with the captivating and viral idea that technology could eradicate the barriers between individuals who wanted to share the resources they had. This led to the sudden much-hyped explosion of so-called "sharing economy" marketplace start-ups around 2010. However, research that I led showed that idealistic entrepreneurs misunderstood or forgot the basics of human economic behavior and my team's findings predicted the demise of all but the companies that were able to compete on classical economic terms (better value for money). I joined one such company, Lyft, because I shared the founders' vision for more sustainable transportation. Nevertheless, Lyft and the other rideshare and disruptive transportation companies must all compete fiercely to survive. It's a challenging road ahead, with many obstacles to overcome, but the destination is one I remain deeply committed to; I am still an idealist at heart!